Ecology and Control of the Cricket, Gymnogryllus humeralis Walker (Orthoptera, Gryllidae) a Minor Pest of Casuarina equsetifolia forst., Seedlings in Bombay State, with a List of other Pests of Casuarina. - Chatterjee, P. N. (Indian Forester, 1955)
The ecology of the cricket Gymnogryllus humeralis Walker ( Orthoptera, Gryllidae ), a minor pest in the seedling stage of Casuarina equsetifolia, as studied in the field in Western Kanara Forest Division, Bombay State, during 1947-49, is described. Casuarina transplants of two feet and above in height were observed to have outgrown the limit of susceptibility to attack by crickets in the experimental localities, i.e., Chittakula (Karwar forest range), Harvada (Ankola forest range) and Kaserkode (Honavar forest range). The cricket is polyphagous and feeds upon various food-plants besides casuarina. They avoid poisoned food and so it was found difficult to poison-bait them in the field. In cages, in the laboratory, however, when no alternative food-plant was supplied they ate poisoned casuarina needles and died. Gymnogryllus humeralis has three generations in Peninsular India. In the insectary at Dehra Dun it passed through one complete and a part of the second generation; in the latter generation, it died in the nymphal stage in the severe winter of North India. Other insect pests of casuarina are also recorded.